Challenges and adaptation on online learning during COVID-19 pandemic - Salasiah Ammade; Ali Wira Rahman; Syawal Syawal (Intelektual Pustaka Media Utama, 2022)
Coronavirus Disease (COVID-19) has impacted the continuity of learning in education aspects. This research aimed to analyze the challenges and the adaptative strategy of online learning for urban vocational school teachers and students during COVID-19. The research applied a descriptive qualitative design in supporting the data needed. The sample of the study was taken randomly from a vocational school in Indonesia consisting of seven students and four teachers in English subject teaching class. In gathering the data, observation and interview were used as research instrument and it was analyzed using Braun’s thematic analysis. The data gathered revealed that vocational school students face some challenges when learning online in English teaching subject during COVID-19 pandemic and did the adaptation dealing with the situation. The interview exposed the challenge faced by the vocational school teachers and students during online learning covering lack of lesson understanding, low creativity in using learning sources, lack of psychological bond with the teacher, internet stability, lack of face meeting exposure, and learning accessibility. The adaptive strategy implemented by the respondents mainly link with technical stuff like stabilizing internet coverage, searching the learning resource more intensive, and providing learning module.